JUSTICE AND SOCIAL CHANGE FOR INCLUSIVE EDUCATION IN INDONESIA AND ASEAN FOR DISABLED PERSONS (STUDY ON PEOPLE AFFECTED BY LEPROSY) - Tarigan, Nuah Perdamenta; Siregar, Christian; Tampubolon, Simon Mangatur (SEEIJ (Social Economics and Ecology International Journal), 2017)
Justice that has not existed and is apparent among the disabilities in Indonesia is very large and spread in the archipelago is very large, making the issue of equality is a very important thing especially with the publication of the Disability Act No. 8 of 2016 at the beginning of that year. Only a few provinces that understand properly and well on open and potential issues and issues will affect other areas including the increasingly growing number of elderly people in Indonesia due to the increasing welfare of the people. The government of DKI Jakarta, including the most concerned with disability, from the beginning has set a bold step to defend things related to disability, including local governments in Solo, Bali, Makassar and several other areas. Leprosy belonging to the disability community has a very tough marginalization, the disability that arises from leprosy quite a lot, reaches ten percent more and covers the poor areas of Indonesia, such as Nusa Tenggara Timur, Papua, South Sulawesi Provinces and even East Java and West Java and Central Java Provinces. If we compare again with the ASEAN countries we also do not miss the moment in ratifying the CRPD (Convention of Rights for People with Disability) into the Law of Disability No. 8 of 2016 which, although already published but still get rejections in some sections because do not provide proper empowerment and rights equality. The struggle is long and must be continued to build equal rights in all areas, not only health and welfare but also in the right of the right to receive continuous inclusive education.